Tehpai as an Expression of Filial Piety - Sutami, Hermina; Rahmawati Kabul, Assa (KnE Social Sciences, 2022)
Tehpai is one of the events in the series of wedding ceremonies for Indonesians of Chinese descent, for both the Peranakan and the Totok. This ceremony is not religious, and is a custom that has been carried out for hundreds of years. In this modern era, the tehpai custom is still carried out as a cultural ceremony. Why is this custom not considered out of date? What is the thought or idea behind this sustainable tehpai? This ingrained custom is believed to have a philosophical background, from the teachings of Confucius. The purpose of this research was to explore the teachings of Confucius that underlie the tehpai event in the Chinese wedding ceremony. Peirce’s theory of semiotics was used to explain the philosophical background. This research found that the concepts of filial piety and family relationship from the teachings of Confucius underlie the tehpai event in the wedding ceremony of those of Chinese descent in Indonesia. Keywords: tehpai, Indonesian Chinese descent, filial piety, Confucius